(untitled) (Discourse of Law and Administration, 2022)
Three documents are the key legal acts of the European Union: (1) Single European Act, international agreement of 1986, (2) Maastricht Treaty (officially the Treaty on European Union), international agreement signed in 1992, (3) The Treaty of Amsterdam, an international agreement signed in 1997. They are the basis for countless legal acts, including the rules for the functioning of structural funds, which are a source of financing and assistance for Member States in many areas of life, from infrastructure to social matters. The basic EU funds are the European Regional Development Fund, the European Social Fund and the Cohesion Fund. Since joining the EU on May 1, 2004, Poland is still the largest aid beneficiary. As of January 2016, since the beginning of its membership in the European Union, Poland has received almost EUR 140 billion. At the same time, we paid over EUR 46.7 billion to the EU. EU aid is directed mainly to infrastructure, agricultural areas, environmental protection, new technologies and social needs. Creating the next EU budget for the next seven-year financial perspectives is a difficult and long process. We expect that in the new 2021-2027 perspective, we will receive EUR 64.4 billion and will continue to be the largest beneficiary of aid among EU Member States, which will allow for a smooth exit from the ongoing COVID-19 pandemic.